Influence of antioxidants on oxidative stability of the oil Chia (Salvia hispanica L.) by rancimat (Scientia Agropecuaria, 2017)
Oxidative rancidity, known as autoxidation, is the main cause of deterioration of oils and fats, which can be controlled by the use of antioxidants increasing oxidative stability and shelf life. Chia oil is rich in polyunsaturated fatty acids (PUFAs), particularly omega-3 (ω-3) and omega-6 (ω-6) beneficial to human health, but PUFAs also favor the reaction of Autoxidation. The aim of this work was to determine the effect of natural and synthetic antioxidants at the concentration of 200 ppm of ethoxyquin (EQ), butylhydrixyanisol (BHA), butylhydroxytoluene (BHT) and fortium (FT), on the oxidative stability index (OSI) of chia oil per rancimat at different temperatures (90, 100 and 110 °C). The rancimat method is included in the AOCS Cd 12b-92 standards, because of its ease of use and reproducibility allows evaluating the OSI in a relatively short period. The results show that between BHT and EQ, as well as between BHA and FT, did not present a statistically significant difference (p ≤ 0.05). The BHT being the antioxidant that increased the chia oil OSI, with a protection factor (PF) of 1.30, 1.26 and 1.29 for the different temperatures applied and with an activation energy (Ea) of 82.75 kJ / mol, therefore, its use would be recommended.
Keywords: chia oil; oxidative stability index; protection factor; activation energy; rancimat